Stomatal Structure in Solidago L. Species as the Index of their Adaptation Opportunities - Vinogradova, Yulia; Grygorieva, Olga; Vergun, Olena (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The study of the adaptability of alien plant species is very important. According to this characteristic there is possible to forecast their further spreading in the secondary distribution range. This is especially relevant for the species having already “escaped” from cultivation and started actively invading the natural communities. Well known that the structure of the leaf blade reflects the adaptability of the species. The purpose of this study is to compare the stomatal structure of cultivated Solidago L. species to assess their adaptive capacity. Alien specimens from the collection of Padova botanical garden (Italy): S. altissima L., S. caesia L., S. canadensis L., S. graminifolia(L.) Salisb., S. juncea Aiton, S. latifolia L., S. lepida DC., S. rugosa Mill., S. sempervirens L., S. serotinoides Á. Löve & D. Löve (= S. gigantea var. leiophylla Fernald), S. uliginosa Nutt. were the objects of the study. The stomata were characterized by 21 quantitative characteristics. Various strategies were being implemented to increase the total transpiration area of plants: increasing the size of stomata; increasing the number of stomata; increasing the area of the leaf blade; increasing the number of leaves on the shoot; increasing the number of the shoots. In terms of the relative transpiration area index (Iot, %), the species are divided into three groups with a high (25–50), medium (15–25) and low (<15) Iot. Our article is considered as a basis for monitoring the dissemination of alien species. The high value of Iot indicates the greater adaptiveness of alien species and can be used to predict the further expansion of their secondary distribution range and increase the chances of transforming into an invasive taxon.